2018
DOI: 10.1111/age.12685
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the interval of a growth QTL on chromosome 4 in laying hens

Abstract: In our previous research, we identified a QTL with an interval of 3.4 Mb for growth on chicken chromosome (GGA) 4 in an advanced intercross population of an initial cross between the New Hampshire inbred line (NHI) and the White Leghorn inbred line (WL77). In the current study, an association analysis was performed in a population of purebred white layers (WLA) with White Leghorn origin. Genotypic data of 130 SNPs within the previously identified 3.4-Mb region were obtained using a 60K SNP chip. In total, 24 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Gu et al identified the same QTL interval, which spanned 8.6 Mb, by performing a GWAS on an F2 chicken resource population derived from a cross between Silky Fowl and White Plymouth Rock [33]. Other studies further narrowed the QTL region to a length of 1.5 Mb, harbouring 15 genes [34,35]. Although we were unable to further narrow the size of the QTL interval in our study due to a strong level of LD and limited SNP density, we identified two significant SNPs with the highest effects and contribution to heritability of growth traits.…”
Section: Comparison With Qtl From Previous Studies and Candidate Genesmentioning
confidence: 96%
“…Gu et al identified the same QTL interval, which spanned 8.6 Mb, by performing a GWAS on an F2 chicken resource population derived from a cross between Silky Fowl and White Plymouth Rock [33]. Other studies further narrowed the QTL region to a length of 1.5 Mb, harbouring 15 genes [34,35]. Although we were unable to further narrow the size of the QTL interval in our study due to a strong level of LD and limited SNP density, we identified two significant SNPs with the highest effects and contribution to heritability of growth traits.…”
Section: Comparison With Qtl From Previous Studies and Candidate Genesmentioning
confidence: 96%
“…Sewalem et al used an F 2 chicken population from a cross of a broiler sire-line and an egg laying (White Leghorn) line to identify QTLs on Chr1, -2, -4, -7, -8, and -13 that affected BW, and Chr4 had the largest single additive effect (Sewalem et al 2002). Researchers identified QTLs on Chr4 that affected growth performance in different varieties and populations (Brandt et al 2017;Jin et al 2015;Li et al 2018), such as a White Leghorn × Rhode Island Red cross (Sasaki et al 2004), a Silky Fowl × White Plymouth Rock cross (Gu et al 2011), Beijing-You chickens (Liu et al 2013), and a population of purebred white layers (WLA) with White Leghorn origin (Lyu et al 2018). In this study, 17 phenotypes, including BW8, BW12, SL12, CWe and the weight of several internal organs, were mapped on Chr4, indicating that genes on Chr4 may have large effects on BW.…”
Section: Figmentioning
confidence: 99%
“…2015 ; Lyu et al . 2017 , 2018 ) detected and progressively fine mapped a region containing 15 genes, including Ligand-dependent nuclear receptor corepressor like ( LCORL; ENSGALG00000014421 ) and Condensin complex subunit 3 ( NCAPG ; ENSGALG00000014425 ). This locus is also associated with body size traits in humans ( Weedon et al .…”
Section: Discussionmentioning
confidence: 99%